2002
DOI: 10.1002/bem.102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent and continuous exposure to electromagnetic fields on cultured hippocampal cells

Abstract: This study was designed to assess the effect of 50 Hz electromagnetic fields (EMFs) on hippocampal cell cultures in the presence or absence of either sodium nitroprusside (SNP, a NO donor) or Fe2+ induced oxidative stress. One week old cultured rat hippocampal cells were exposed to either intermittent EMFs (IEMFs, 50 Hz, 0-5 mT, 1 min ON/OFF cycles, repeated 10 times every 2 h, 6 times/day during 48 h) or continuous EMFs (CEMFs, 50 Hz, 0-5 mT for 48 h). In a second set of experiments, the effect on such EMFs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In this study, we also compared the effects of continuous and intermittent exposure to 50 Hz ELF-MFs. Boland et al (2002) reported that 50 Hz intermittent exposure at high intensities enhanced NO-induced oxidative cell damage in brain cell culture more than continuous exposure did. However, the exposure protocols used in this study show that biochemical parameters were almost equally affected by continuous and intermittent exposures.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we also compared the effects of continuous and intermittent exposure to 50 Hz ELF-MFs. Boland et al (2002) reported that 50 Hz intermittent exposure at high intensities enhanced NO-induced oxidative cell damage in brain cell culture more than continuous exposure did. However, the exposure protocols used in this study show that biochemical parameters were almost equally affected by continuous and intermittent exposures.…”
Section: Discussionmentioning
confidence: 98%
“…While some researchers have reported the existence of potentially dangerous interactions of MF with living organisms [Luben et al, 1982;Adair, 1994;Wertheimer et al, 1995;Ji et al, 1998;Kavet et al, 2000;Boland et al, 2002;Robison et al, 2002;Caprani et al, 2004;Rajendra et al, 2004], other researchers have witnessed no effect [Jackson, 1992;Cantoni et al, 1996;Fanelli et al, 1999;Sweeney et al, 2001;Jenkins et al, 2002;Kainz et al, 2003;Kurokawa et al, 2003;Tripp et al, 2003;Burchard et al, 2004;Moon-Koo et al, 2004]. To evaluate the potential effects of MF, various durations and intensities of field exposure have been studied, as well as different model systems and assay methods.…”
Section: Introductionmentioning
confidence: 97%
“…Living organisms are electrochemical systems that use ELF-EMFs from the structure of proteins to cell-to-cell communication and nervous system functions. The widespread use of electricity increases the potential sources of radiation resulting in continuous and/or intermittent exposure of living beings to ELF-EMFs (Boland et al, 2002). Magnetic flux densities of EMFs of the devices offered by the technology, which make our life easier, vary between 1 × 10 −4 milli Tesla (mT) and 2.5 mT, and this value, which is more than magnetic flux densities of the EMF of human body (10 −7 mT) and natural environment (10 −6 mT) can disrupt the harmony (Seyhan, 2010).…”
Section: Introductionmentioning
confidence: 99%